2020
DOI: 10.1145/3380985
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Study of Unsupervised Domain Adaptation for Robust Human-Activity Recognition

Abstract: Wearable sensors are increasingly becoming the primary interface for monitoring human activities. However, in order to scale human activity recognition (HAR) using wearable sensors to million of users and devices, it is imperative that HAR computational models are robust against real-world heterogeneity in inertial sensor data. In this paper, we study the problem of wearing diversity which pertains to the placement of the wearable sensor on the human body, and demonstrate that even state-of-the-art deep learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 27 publications
0
62
0
1
Order By: Relevance
“…Qin et al [32] propose Adaptive Spatial-Temporal Transfer Learning (ASTTL) to allow more accurate source selection to perform domain adaption. Chang et al [4] have looked into feature matching and adversarial learning in adapting the activity model from one sensor position to another. These recent techniques are built on a similar assumption that both source and target domains share the same feature space so that they can share the same activity model [6] or feature extractor [4], [32].…”
Section: A Domain Adaptation In Human Activity Recognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Qin et al [32] propose Adaptive Spatial-Temporal Transfer Learning (ASTTL) to allow more accurate source selection to perform domain adaption. Chang et al [4] have looked into feature matching and adversarial learning in adapting the activity model from one sensor position to another. These recent techniques are built on a similar assumption that both source and target domains share the same feature space so that they can share the same activity model [6] or feature extractor [4], [32].…”
Section: A Domain Adaptation In Human Activity Recognitionmentioning
confidence: 99%
“…Chang et al [4] have looked into feature matching and adversarial learning in adapting the activity model from one sensor position to another. These recent techniques are built on a similar assumption that both source and target domains share the same feature space so that they can share the same activity model [6] or feature extractor [4], [32]. Domain adaptation on binary sensor data is different from accelerometer data as the main challenge is to tackle heterogeneity of feature spaces.…”
Section: A Domain Adaptation In Human Activity Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such techniques are hard to apply to our problem domain since this still requires enough real training data (atleast in unlabelled form) from IMU to achieve sufficient convergence of the domain adaptation process. Furthermore, each user's finger motion pattern as well as natural variations in sensor wearing positions could lead to different distributions in the sensor data [15,20] thus entailing more training data for each setting. On the other hand, ZeroNet performs comparable to models developed with semi-supervised domain adaptation [27,83] which need partial labelled real IMU data and even outperforms models fully trained on our own real IMU dataset (details in Sec.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent previous work [8], the authors developed and evaluated three adaptation techniques for HAR: data augmentation, feature matching and confusion maximization. They concluded that performing unsupervised domain adaptation and domain generalization for HAR in wearing diversity problem is a very complicated task, and they proposed some practical considerations for unsupervised domain adaptation.…”
Section: Introductionmentioning
confidence: 99%